Do 2H and 18O in leaf water reflect environmental drivers differently?. Issue 1 (12th April 2022) - Cernusak, Lucas A.; Barbeta, Adrià; Bush, Rosemary T.; Eichstaedt (Bögelein), Rebekka; Ferrio, Juan Pedro; Flanagan, Lawrence B.; Gessler, Arthur; Martín‐Gómez, Paula; Hirl, Regina T.; Kahmen, Ansgar; Keitel, Claudia; Lai, Chun‐Ta; et al.
Summary: We compiled hydrogen and oxygen stable isotope compositions (δ 2 H and δ 18 O) of leaf water from multiple biomes to examine variations with environmental drivers. Leaf water δ 2 H was more closely correlated with δ 2 H of xylem water or atmospheric vapour, whereas leaf water δ 18 O was more closely correlated with air relative humidity. This resulted from the larger proportional range for δ 2 H of meteoric waters relative to the extent of leaf water evaporative enrichment compared with δ 18 O. We next expressed leaf water as isotopic enrichment above xylem water (Δ 2 H and Δ 18 O) to remove the impact of xylem water isotopic variation. For Δ 2 H, leaf water still correlated with atmospheric vapour, whereas Δ 18 O showed no such correlation. This was explained by covariance between air relative humidity and the Δ 18 O of atmospheric vapour. This is consistent with a previously observed diurnal correlation between air relative humidity and the deuterium excess of atmospheric vapour across a range of ecosystems. We conclude that 2 H and 18 O in leaf water do indeed reflect the balance of environmental drivers differently; our results have implications for understanding isotopic effects associated with water cycling in terrestrial ecosystems and for inferring environmental change from isotopic biomarkers that act as proxies for leaf water.